Disorder of Sexual Development and Congenital Heart Defect in 47XYY: Clinical Disorder or Coincidence?. (15th June 2015) - Latrech, Hanane; Skikar, Imane; Gharbi, Mohammed El Hassan; Chraïbi, Abdelmjid; Gaouzi, Ahmed
Abstract : Background . 47XYY syndrome is a rare sex chromosome variation characterized by an additional Y chromosome. Most patients with 47XYY karyotype have normal phenotype. This disorder seems associated with a higher risk of developing behavioral and cognitive problems, tall stature, and infertility in adulthood. Sexual development disorder is a rare finding. We report a first case with an abnormal left coronary artery originating from the pulmonary artery in a 47XYY patient. Case . A one-month-old child was referred for ectopic testis and micropenis. Physical examination revealed facial dysmorphia, micropenis, and curvature of the penis with nonpalpable testis. Laboratory tests showed decreased total testosterone and anti-Mullerian hormone (AMH) levels. Blood karyotyping revealed a 47XYY chromosomal formula. At the age of 3 months, the patient developed dyspnea and tachycardia. Echocardiography revealed an anomalous left coronary artery from pulmonary artery with left ventricular dysfunction requiring surgical revascularization by direct reimplantation of the left coronary artery system. Our second case was a 3-year-old child referred for hypospadias with nonpalpable left testicle. Physical examination showed hypertelorism. Blood karyotyping revealed a 47XYY chromosomal formula. Conclusion . To our knowledge, this is the first case of 47XYY syndrome associated with this congenital heart malformation and a sexual development disorder.